Operação de Sistemas de Distribuição Incluindo Veículos Elétricos e Recursos Energéticos Renováveis - Pedro Dias Lopes Coimbra (2018)
Many advantages are conducted by Electric vehicles (EVs) like increasing the efficiency and reliability of distribution systems, as well as decreasing the dependence on oil and CO2 gas emissions. EVs also offer a unique advantage in terms of a technology known as vehicle to grid (V2G). The V2G concept is essentially the ability of EVs to inject electrical power into the distribution systems. Therefore, EVs can act either as a load or as a distributed storage device. Due to the growth of EVs in the future, management and operation of distribution systems are more important than in the past. EV owners do not use the vehicles overall 93 to 96 percent of day-time. T he high numbers of EVs with having V2G capability can provide a good opportunity for the operation of distribution systems, if the charging/discharging of EVs is managed. Also, renewable energy resources (RERs) play a critical role in the future distribution systems. Therefore, distribution systems should be operated based on the presence of renewable energy resources and electric vehicles.